ANALISIS HUBUNGAN PATRON-KLIEN (STUDI KASUS HUBUNGAN TOKE DAN PETANI SAWIT POLA SWADAYA DI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU) - Kausar '; Komar Zaman (Indonesian Journal of Agricultural Economics, 2011)
Smallholder farmers in swadaya scheme continuously depend on wholesalers as thefarmers need the wholesalers to market their oil palm Fresh Fruit Bunches (FFB) to theoil palm factory. Relationship among wholesalers (toke) and smallholder farmers isreferred to as the patron-client relationship. In such a relationship, the wholesalers arecalled patron, while smallholders are called clients. The research objective was todetermine the marketing channels of oil palm fresh fruit bunches (FFB) of swadaya-scheme farmers and to analyze the factors which lead to patron-client relationship. Theresearch was conducted in Mahato and North Tambusai Village, North Tambusai Sub-District, Rokan Hulu District. This research used survey method. Sampling for oil palmfarmers was conducted by multistage random sampling. There are three marketingchannels of FFB identified. Marketing Channel 1 starts from farmers to wholesalers(non SPB) to wholesalers (SPB), where the non-SPB wholesalers only use the SPB ofthe SPB wholesalers to sell to oil palm factory. Marketing channel 2 starts from farmersto wholesalers (non SPB), to wholesalers (SPB) and then to the factory. MarketingChannel 3 starts from farmers to wholesalers (SPB) and to the factory. Factorsinfluencing the formation of patron-client relationship among wholesalers (toke) andsmallholders are: (1) FFB marketing of farmers highly depends on the wholesalers, (2)high farming costs, and (3) farmers are tied with a lot of debt to wholesalers foreveryday needs, children's education and health cost.Keywords: patron-client, toke (wholesalers), marketing channels, oil palm